“Si no se habla, no existe”: comparación en la cobertura mediática a la comunidad LGBTIQ+ en los programas de ATV noticias, Willax y Capital TV en junio del 2018 y junio del 2019 - Valle Marroquín, María Laura (2020)
Although it is true that the Peruvian press still has a long way to go in terms of ways of reporting, this paper will study how media coverage has been changing, focusing on the notes published in the ATV Noticias programs, Willax and Capital TV in 2018 and 2019. Throughout these paragraphs we have talked about the situation of inequality that these people face, so we consider that talking about a disadvantaged population allows us to become aware of our professional work , regardless of the area to which we dedicate ourselves, in favor of a more just and egalitarian society. The question that will guide us when making this article is: "How much has the media coverage of the LGTB + community varied in the ATV Noticias, Willax and Capital TV programs in June 2018 and June 2019?", And we will look first , to demonstrate that said coverage has been improving, as we mentioned above, since it seeks to objectively report a journalistic event, such as a mass march, which allows viewing and debate, not only in private or family settings, but also in the public spheres.